2015
DOI: 10.1175/mwr-d-14-00300.1
|View full text |Cite
|
Sign up to set email alerts
|

A Vertically Flow-Following Icosahedral Grid Model for Medium-Range and Seasonal Prediction. Part I: Model Description

Abstract: A hydrostatic global weather prediction model based on an icosahedral horizontal grid and a hybrid terrainfollowing/isentropic vertical coordinate is described. The model is an extension to three spatial dimensions of a previously developed, icosahedral, shallow-water model featuring user-selectable horizontal resolution and employing indirect addressing techniques. The vertical grid is adaptive to maximize the portion of the atmosphere mapped into the isentropic coordinate subdomain. The model, best described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 91 publications
0
23
0
Order By: Relevance
“…Research teams from National Center for Atmospheric Research (NCAR)'s Community Earth System Model (CESM) (Kim et al 2013), Weather Research and Forecasting (WRF) Model (Michalakes et al 2016), and the FV3 (Nguyen et al 2013) reported little to no performance gain compared to the CPU. A more comprehensive parallelization for the MIC with National Oceanic and Atmospheric Administration (NOAA)'s Flow-Following Finite-Volume Icosahedral Model (FIM) (Bleck et al 2015) included dynamics and physics running on the MIC (Rosinski 2015). Execution of the entire model on the KNC gave no performance benefit compared to the CPU.…”
mentioning
confidence: 99%
“…Research teams from National Center for Atmospheric Research (NCAR)'s Community Earth System Model (CESM) (Kim et al 2013), Weather Research and Forecasting (WRF) Model (Michalakes et al 2016), and the FV3 (Nguyen et al 2013) reported little to no performance gain compared to the CPU. A more comprehensive parallelization for the MIC with National Oceanic and Atmospheric Administration (NOAA)'s Flow-Following Finite-Volume Icosahedral Model (FIM) (Bleck et al 2015) included dynamics and physics running on the MIC (Rosinski 2015). Execution of the entire model on the KNC gave no performance benefit compared to the CPU.…”
mentioning
confidence: 99%
“…FIM‐Chem model is used to generate the nature run. FIM is a global Flow‐following finite‐volume Icosahedral Model (http://fim.noaa.gov/) [ Bleck et al ., ] developed in the Global Systems Division of NOAA Earth System Research Laboratory. By integrating FIM and GOCART aerosol chemistry scheme [ Chin et al ., , ], FIM‐Chem simulates and forecasts aerosol and gas‐phase species at various spatial resolutions and with different levels of complexity [ Grell et al ., ; Zhang et al ., ].…”
Section: Methodsmentioning
confidence: 99%
“…Conventionally, such a construction is referred to as layer‐averaged discretization, which was used by some isopycnal models (e.g., Bleck, ; Oberhuber, ) or the Arbitrarily Lagrangian Eulerian framework (e.g., Adcroft & Campin, ; Ringler et al, ) in the ocean modeling community. For atmospheric modeling, it is also convenient for some vertically Lagrangian models (e.g., Chen et al, ; Lin, ) or quasi‐Lagrangian models (e.g., Bleck et al ) to adopt such a construction. In a quasi‐Lagrangian approach, for example, an isentropic coordinate for the atmosphere, trueη̇ remains zero in the adiabatic condition so that no flux goes across the coordinate face.…”
Section: Model Descriptionmentioning
confidence: 99%